2022
DOI: 10.1038/s41467-022-34476-2
|View full text |Cite|
|
Sign up to set email alerts
|

CBP-HSF2 structural and functional interplay in Rubinstein-Taybi neurodevelopmental disorder

Abstract: Patients carrying autosomal dominant mutations in the histone/lysine acetyl transferases CBP or EP300 develop a neurodevelopmental disorder: Rubinstein-Taybi syndrome (RSTS). The biological pathways underlying these neurodevelopmental defects remain elusive. Here, we unravel the contribution of a stress-responsive pathway to RSTS. We characterize the structural and functional interaction between CBP/EP300 and heat-shock factor 2 (HSF2), a tuner of brain cortical development and major player in prenatal stress … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Unlike HSF1, HSF2 is considered an unstable protein under normal growth conditions, and the expression of HSF2 is tightly regulated both at the mRNA and protein levels, via microRNAs and the ubiquitin-proteasome system. 30 , 43 , 52 , 53 Consequently, we were surprised to detect prominent cytoplasmic HSF2 expression in all studied smooth muscle cells, endothelial cells, and myoepithelial cells ( Table 1 ). The significant difference in signal intensity compared to cell lines, which typically display nuclear HSF2 expression, shows that HSF2 is differently regulated in intact tissues.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Unlike HSF1, HSF2 is considered an unstable protein under normal growth conditions, and the expression of HSF2 is tightly regulated both at the mRNA and protein levels, via microRNAs and the ubiquitin-proteasome system. 30 , 43 , 52 , 53 Consequently, we were surprised to detect prominent cytoplasmic HSF2 expression in all studied smooth muscle cells, endothelial cells, and myoepithelial cells ( Table 1 ). The significant difference in signal intensity compared to cell lines, which typically display nuclear HSF2 expression, shows that HSF2 is differently regulated in intact tissues.…”
Section: Discussionmentioning
confidence: 92%
“…This finding is particularly intriguing considering the recent findings linking HSF2 to the maintenance of cell–cell adhesion contacts. 14 , 30
Fig. 5 Cross-section of cardiac muscle tissue.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…She showed that PAE provokes immediate changes in DNA methylation in the mouse developing cortex, which are associated with immediate modifications of gene expression, seem also to persist later in life, and are thus potential biomarkers for the diagnosis and follow-up of at-risk children. Interestingly, stress-responsive transcription factors of the immune/inflammatory pathway (Schang et al 2021 ) and HSFs (de Thonel et al 2022 ) represent the holes in the defense of the developing brain. They are unexpectedly active and necessary for physiological brain development and are deeply disturbed by prenatal stress.…”
Section: Cellular Stress Responsesmentioning
confidence: 99%
“…Other cancer models have revealed that HSF2 can either promote or suppress cancer cell growth (Mustafa et al, 2010; Zhong et al, 2016; Meng et al, 2017; Yang et al, 2019; Smith et al, 2022). At the cellular level, maintenance of HSF2 expression is required for cell-cell adhesion contacts (Joutsen et al, 2020; de Thonel et al, 2022). To date, no HSF2-specific gene program supporting tumorigenesis has been identified, and the signaling pathways regulating HSF2 expression and its activity during malignant transformation remain to be uncovered.…”
Section: Introductionmentioning
confidence: 99%